Pengaruh Penambahan Garam Dapur dan Pupuk Urea Terhadap CBR Tanah Lempung Lunak - Mangasik, Setiawan Anugerah; Sariman, Syahrul; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Soil is the most important part to support construction, one of which is soft clay soil which has a high-water content so that the CBR of soft clay soil is low and causes a decrease in the soil's bearing capacity. This research aims to determine the effect of adding urea fertilizer and table salt on the CBR value of soft clay soil. The percentages used in this research were 10% urea fertilizer and 5%, 10%, 15% table salt. The results of the soil characteristics test, passing sieve No.200 was 83.60%, liquid limit 54.04%, plastic limit 24.07%, shrinkage limit 18.71% and plasticity index 28.97%. According to AASHTO land is included in category A-7-5 while according to USCS land is included in category CH. From the results of the specific gravity examination, the specific gravity was found to be 2.653, this soil is included in the organic clay soil category which has a specific gravity value between 2.58-2.65. The maximum CBR value occurred when adding 10% urea fertilizer + 15% table salt with a CBR value of 21.68%.